Analysis of Factors Influencing the Economic Growth in West Java Province - Fachrozi, Reza (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyse the factors that influence the economic growth of West Java Province. These factors include foreign investment, domestic investment, health, education and infrastructure. This study uses panel data regression analysis on secondary data of 18 regencies and 9 cities in West Java Province in 2017-2022. The results showed that foreign investment, education and infrastructure tend to have an impact on increasing economic growth in West Java Province. Domestic investment and health have no effect on increasing economic growth in West Java Province. The implication of the findings in this study is that the West Java government needs to increase the attractiveness of foreign and domestic investment and allocate investment to strategic sectors that have great potential for economic growth. In addition, increasing economic growth can be achieved by improving the quality of health and education, as well as strengthening infrastructure, especially water infrastructure. Thus, it can encourage the acceleration of economic growth and improve the welfare of the people in West Java Province.